1985
DOI: 10.4141/cjps85-007
|View full text |Cite
|
Sign up to set email alerts
|

APPEARANCE OF FUNGUS, ERGOSTEROL AND Fusarium MYCOTOXINS IN THE HUSK, AXIAL STEM AND STALK AFTER EAR INOCULATION OF FIELD CORN

Abstract: (Miller et al. 1983b). This paper reports on the subsequent appearance of the fungus, ergosterol and mycotoxins in the husk, axial stem and stalk. MATERIALS AND METHODS Inoculation and Sampling of CornFull details of the methods used are given by Miller et al. (1983b). In summary, ears of corn were inoculated by a toothpick method with Fusarium graminearum isolate M69 and plants were taken at random at weekly intervals from 2 to 9 wk thereafter. The ears were husked, the plant stalks were cut into 10-cm sectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

1986
1986
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 4 publications
3
18
0
Order By: Relevance
“…The same metabolites have been detected in all fractions of maize samples. According to other reports (Young and Miller., 1985;Bennett et al, 1988;Perkowski et al, 1991) the highest amounts of DON were present in axial stem. In hybrids examined in this paper, the following DON concentrations were found in axial stem ranged from 153 mg/kg (Ruten) to 1962 mg/kg (RAH BE 86101).…”
Section: Resultssupporting
confidence: 59%
See 1 more Smart Citation
“…The same metabolites have been detected in all fractions of maize samples. According to other reports (Young and Miller., 1985;Bennett et al, 1988;Perkowski et al, 1991) the highest amounts of DON were present in axial stem. In hybrids examined in this paper, the following DON concentrations were found in axial stem ranged from 153 mg/kg (Ruten) to 1962 mg/kg (RAH BE 86101).…”
Section: Resultssupporting
confidence: 59%
“…Accumulation of mentioned metabolites in naturally infected ears have been reported in our previotis papers (Visconti et al, 1990;Perkowski et al, 1991). Miller and Young (1983) and Young and Miller (1985) studied the formation of DON, 15-AcDON and zearalenone in field com in ear and adjacent parts of stalk. They found toxins throughout the plant, but mainly in the infected part (ear).…”
Section: Introductionmentioning
confidence: 89%
“…As mentioned above, metabolite penetration into the kernels is limited when humidity is high, when mycotoxins accumulate mostly on the kernels surface. Literature data and our earlier findings (Young and Miller 1985;Perkowski et al 1990) indicated that the outer portions, i.e. chaff and husk, have higher mycotoxin contamination levels, which is an interesting finding with practical implications.…”
Section: Resultsmentioning
confidence: 84%
“…Trichothecenes apparently are not essential for fungal growth in vitro, because field strains and mutants that do not produce trichothecenes grow as vigorously as trichothecene-producing strains in the laboratory (10). Some studies have suggested that trichothecenes may be translocated in the plant tissues in advance of fungal growth (29,35). As trichothecenes probably act to impair protein synthesis in plants, trichothecenes could suppress or delay the plant defense response against a fungal attack.…”
Section: Discussionmentioning
confidence: 99%